On Time Dependent Entropy vis-a-vis Clausius Inequality: Some of the Aspects Pertaining to the Global and the Local Levels of Thermodynamic Consideration - A. Bhalekar, Anil (Asian Journal of Chemistry, 2010)
Meixner's revelation in connection with the nonclarity about the entropy function contained in the differential form of Clausius' inequality led us to reinvestigate the foundational aspects involved therein. It is proved that the differential form of Clausius' inequality contains the entropy function for nonequilibrium states. We have also augmented the cyclic form of the Clausius' inequality to include those nonequilibrium situations wherein the system simultaneously interacts at the different positions of its bounding surface with the heat reservoirs of different temperatures. It gets once again established that no local level Clausius' inequality analogue can ever be devised if the system has a spatial nonunifonnity. Contrary to Meixner's apprehension one obtains an unique time dependent entropy function from the cyclic fonn of Clausius' inequality.